Katherine Mansfield : the early years - Kimber, Gerri (Katherine Mansfield Studies Eup., 2016)
Focusing on the first 20 years of Katherine Mansfield's life, from her birth in 1888 to her final departure from New Zealand in 1908, this biography reveals the importance of Mansfield's childhood and adolescent years to her development as a writer and offers unique insights into her New Zealand stories. Gerri Kimber draws on detailed reminiscences of Mansfield's former school friends and acquaintances, early letters, personal papers, notebooks and family papers as well as on previously unused archive material and photographs. Kimber illuminates Mansfield's home life and school days, her friendships, first infatuations and sexual experimentation both with young men and young women and reveals the effect Mansfield's experiences had on her earliest stories. What emerges is a fascinating picture of a feisty and imaginative young girl who would turn into an expressive, non-conformist adolescent: the unruly Kass Beauchamp who would become Katherine Mansfield, the celebrated modernist writer. The first biography of Katherine Mansfield's early years since 1933. Focusing on the first nineteen years of Katherine Mansfield's life, from her birth in 1888 to her arrival in London in 1908 to be a writer, this new biography sheds new light on Mansfield's childhood and teenage years as well as on her development as a writer. The biography draws extensively on previously unused archive material, including the research papers assembled by Ruth Elvish Mantz for her 1933 biography of Mansfield, detailed reminiscences of former school friends and acquaintances, Mansfield's autograph book, birthday book, her early letters, notebooks and family papers. Using this rich seam of material, Gerri Kimber explores Mansfield's home life and school days, her friendships, first infatuations and sexual experimentation both with young men and young women and her travels through the volcanic North Island of New Zealand and examines her earliest published stories which appeared in school magazines. What emerges is a picture of a feisty, mischievous, young girl and an expressive, non-conformist teenager: the unruly Kass Beauchamp who became Katherine Mansfield, the famous modernist writer. Key Features. Brings to light a period of Mansfield's life previously of little interest to biographers Presents a new image of Mansfield as a child and young woman Reveals how her youthful experiences fashioned both her later personality and the content of much of her acclaimed adult writing Discussion of the biographical elements present in Mansfield's New Zealand stories